THE COST OF DEBT, DIMENSION OF THE AUDITOR AND JOINT AUDITORS: THE CASE OF THE LARGEST EUROPEAN COMPANIES - Pais, C. (XVI Encuentro AECA (Recuperação económica: confiança e investimento na Europa, 2014)
Using a sample of the largest European companies for the period of 2005 to 2012, we examine the impact of the dimension of the audit companies and the numbers of the auditors in their cost of debt, as there a few studies of this type in Europe. To the extent that is linked to the dimension of the auditor and the joint auditors a higher quality of auditing it is likely that the cost of debt decreases if the dimension and number of auditors increases. The results confirm this assumption, the decrease in the cost of the debt for companies audited by larger auditors and joint auditors, confirming the usefulness of the auditing, despite the recent change on the European Directive of auditing, to reinforce the quality of auditing.